La paz como concepto y derecho: estudio sobre la paz en la Constitución Política de Colombia del año 1991 - Zuluaga, Jhon Wilmar Montoya (2018)
Through this research work has sought to establish what is the constitutional sense that the right to peace has acquired to be embodied in the Constitution of Colombia of 1991, the basic hypothesis of this work is to demonstrate that peace is not the absence of conflicts within society, but mediation and reasonable treatment thereof. In order to demonstrate this hypothesis, a study of the different types of violence according to the Norwegian theoretician Johan Galtung's conceptions is made, trying to establish which are the causal factors of violence, those that prevent the achievement of peace, from that moment on to be identified the specific concept of peace and its conception as a right. Additionally, a historical analysis of the need and the clamor for peace that represented the process and the issuance of the Political Constitution of 1991 in Colombia is presented, a normative and jurisprudential study is carried out in order to establish the relevance and constitutional meaning of the right to peace in Colombia and a concept is formulated regarding the implications of the agreement for the termination of the armed conflict of the Colombian government and the FARC guerrillas against the constitutional right to peace to finally establish a diagnosis of the effective application of said agreement and the effective achievement of peace in Colombia.